Myclobutanil worsens nonalcoholic fatty liver disease: An in vitro study of toxicity and apoptosis on HepG2 cells. (16th November 2016) - Stellavato, Antonietta; Lamberti, Monica; Pirozzi, Anna Virginia Adriana; de Novellis, Francesca; Schiraldi, Chiara
Highlights: Hepatic toxicity of myclobutanil exacerbates fatty acid-induced steatosis. Myclobutanil reduces viability of HepG2 cells to <50% at 100 ppm and to <10% at 500 ppm. Myclobutanil modifies the function of enzymes such LDH and cytochrome c. Analysis of biomarkers such as Bcl-xL/Bak and Mcl-1/Bak confirmed activation of cell death pathways at low doses of myclobutanil. Abstract: Myclobutanil is a conazole class fungicide widely used as an agrichemical. It is approved for use on fruit, vegetables and seed commodities in the EU and elsewhere to control fungi such as Ascomycetes, Fungi Imperfecti and, Basidiomycetes . Its widespread use has raised the issue of possible health risks for agrarian communities and the general population, which can be exposed to residues present in food and drinking water. The toxicities identified include adverse effects on liver and kidney and on the development of male reproductive organs. Since the liver is the first-line organ in the defense against xenobiotics, toxic effects on hepatic metabolism cause degeneration, necrosis, and tissue hypertrophy. Therefore, we investigated myclobutanil's effects on the human liver cell line HepG2. We found that myclobutanil increases the amount of fatty acids in these hepatic cells, as evaluated with Oil Red O staining, and progressively reduces cell viability from 1 ppm to 500 ppm. Analysis of biomarkers such as Bcl-xL/Bak and Mcl-1/Bak confirmed activation of cell death pathways at low doses. Therefore, myclobutanil may play an important role in the pathogenesis and progression of chronic hepatocellular diseases in humans.